1999
DOI: 10.1042/bj3410147
|View full text |Cite
|
Sign up to set email alerts
|

The DmpA aminopeptidase from Ochrobactrum anthropi LMG7991 is the prototype of a new terminal nucleophile hydrolase family

Abstract: The DmpA (d-aminopeptidase A) protein produced by Ochrobactrum anthropi hydrolyses p-nitroanilide derivatives of glycine and d-alanine more efficiently than that of l-alanine. When regular peptides are utilized as substrates, the enzyme behaves as an aminopeptidase with a preference for N-terminal residues in an l configuration, thus exemplifying an interesting case of stereospecificity reversal. The best-hydrolysed substrate is l-Ala-Gly-Gly, but tetra- and penta-peptides are also efficiently hydrolysed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…A blast search indicated that the amino acid sequence deduced from bapA was similar to those of hypothetical protein PA1486 from Pseudomonas aeruginosa PAO1 [17], putative d-aminopeptidase PP3844 from Pseudomonas putida KT2440 [18], hypothetical protein PLU2258 similar to d-aminopeptidase from Photorhabdus luminescens (ssp. laumondii) TTO1 [19], aminopeptidase Atu5242 from Agrobacterium tumefaciens C58 plasmid AT [20] and DmpA (l-aminopeptidase d-Ala-esterase ⁄ amidase) from O. anthropi LMG7991 [15] (Table 1). Figure 3 shows the alignment of the primary structures of BapA from Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A blast search indicated that the amino acid sequence deduced from bapA was similar to those of hypothetical protein PA1486 from Pseudomonas aeruginosa PAO1 [17], putative d-aminopeptidase PP3844 from Pseudomonas putida KT2440 [18], hypothetical protein PLU2258 similar to d-aminopeptidase from Photorhabdus luminescens (ssp. laumondii) TTO1 [19], aminopeptidase Atu5242 from Agrobacterium tumefaciens C58 plasmid AT [20] and DmpA (l-aminopeptidase d-Ala-esterase ⁄ amidase) from O. anthropi LMG7991 [15] (Table 1). Figure 3 shows the alignment of the primary structures of BapA from Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…DmpA has been reported to be a homotetrameric enzyme, each subunit of which is composed of two polypeptides generated by a possible autocatalytic cleavage of a precursor polypeptide. Interestingly, DmpA changes its stereoselectivity depending on the substrate, catalyzing the l-stereoselective hydrolysis of peptides and d-stereoselective hydrolysis of amino acid amides and esters [15]. The gel-filtration chromatography and SDS ⁄ PAGE analysis of the purified BapA revealed that the number of subunits in the native form and the polypeptide composition of each subunit were significantly similar to those for DmpA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, DmpA, an N-terminal nucleophile hydrolase, exhibits different stereospecificities according to the nature of the substrates. It hydrolyses D-alanyl-amide,p-nitroanilide and -methylester more efficiently than their L-counterparts but is a strict L-aminopeptidase with peptides (Fanuel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This may be the case for d-aminopeptidase from Ochrobactrum anthropi in particular, as it is capable of hydrolysing not only d-amino acid amides and d-amino acid p-nitroanilides but also l-amino acid p-nitroanilides (Asano et al 1989). Furthermore, the second d-aminopeptidase from O. anthropi, DmpA, exhibits different stereospecificity as a function of substrate type (Fanuel et al 1999). It hydrolyses d-alanyl-amide, -pNa,methyl-ester more efficiently than their l-counterparts but is a strict l-aminopeptidase with peptides.…”
Section: The Role Of Peps In Nitrogen Supply and Other Cellular Functmentioning
confidence: 99%